Postvaccination Influenza 2009 H1N1 Respiratory Failure Requiring Extracorporeal Membrane Oxygenation - Michael S. Firstenberg; Erik Abel; Danielle Blais; Juan Crestanello; Julie E. Mangino (Case Reports in Infectious Diseases)
The spread of pandemic Influenza A (H1N1-2009) was believed to have been attenuated by the effectiveness of worldwide vaccination initiatives. Despite the immunogenicity of a safe vaccine, we report a case of vaccine failure resulting in catastrophic influenza-associated respiratory failure.